2011
DOI: 10.1007/s00251-011-0554-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the IL17 receptor family in chordates: a new subfamily IL17REL

Abstract: The human interleukin 17 receptor (IL17R) family plays a critical role in inflammatory responses and contributes to the pathology of many autoimmune diseases. So far, five members, IL17RA to IL17RE, have been identified. Recently, some IL17R genes have been identified in non-mammalian species, such as zebrafish IL17RD; however, there are no reports on the evolutionary history of this complex gene family through comparative phylogenetic approaches. Here, we concentrated on the IL17R evolution in chordates. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…According to analysis of the phylogenetic relationship between the various IL-17R protein family members, trout IL-17RA clustered with the other piscine and homeotherm IL-17RA molecules. Multiple alignment of this protein sequence with those of other vertebrate IL-17RA molecules revealed a high degree of conservation within the extracellular and intracellular SEFIR domains, which are characteristic of the IL-17RA family (18,24,25). Several conserved cysteines, eight of which are potentially involved in disulfide bridge formation, as seen in mammalian molecules (64), were also present in trout IL-17RA.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…According to analysis of the phylogenetic relationship between the various IL-17R protein family members, trout IL-17RA clustered with the other piscine and homeotherm IL-17RA molecules. Multiple alignment of this protein sequence with those of other vertebrate IL-17RA molecules revealed a high degree of conservation within the extracellular and intracellular SEFIR domains, which are characteristic of the IL-17RA family (18,24,25). Several conserved cysteines, eight of which are potentially involved in disulfide bridge formation, as seen in mammalian molecules (64), were also present in trout IL-17RA.…”
Section: Discussionmentioning
confidence: 93%
“…Several conserved cysteines, eight of which are potentially involved in disulfide bridge formation, as seen in mammalian molecules (64), were also present in trout IL-17RA. Two putative FNIII domains which are known to be crucial in the binding of the ligand to its receptor (25) were also identified within the extracellular domain of trout IL-17RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, a SEFIR protein was observed in bacterium Staphylococcus hominis (Novatchkova et al, 2003), and later, we found that SEFIR proteins are widely distributed in metazoans (Wu et al, 2011a(Wu et al, , 2011b. Nevertheless, little information about the prokaryotic SEFIR homologues has been reported so far.…”
Section: Introductionmentioning
confidence: 85%
“…However, it is unknown whether the sequences of the signal peptides were cleaved or the proteins do not possess a signal peptide inherently. Chordate CIKSs and IL17Rs contain two TRAF (tumor necrosis factor receptor-associated factor) binding sites: TRAF2 and TRAF6 binding sites (Gaffen, 2009;Li, 2008;Wu et al, 2011aWu et al, , 2011b. TRAF binding sites are also present in prokaryotic SEFIR proteins.…”
Section: Prokaryotic Sefir Proteins Features and Architecturementioning
confidence: 98%